2011
DOI: 10.1371/journal.pone.0017879
|View full text |Cite
|
Sign up to set email alerts
|

Inside Out: Modern Imaging Techniques to Reveal Animal Anatomy

Abstract: Animal anatomy has traditionally relied on detailed dissections to produce anatomical illustrations, but modern imaging modalities, such as MRI and CT, now represent an enormous resource that allows for fast non-invasive visualizations of animal anatomy in living animals. These modalities also allow for creation of three-dimensional representations that can be of considerable value in the dissemination of anatomical studies. In this methodological review, we present our experiences using MRI, CT and μCT to cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 27 publications
2
76
0
Order By: Relevance
“…For instance, Ruffins et al (2007) produced a 3D atlas for quail development at an isotropic voxel resolution of 40-70 μm 3 using an 11.7 T pre-clinical MRI system. In contrast, Lauridsen et al (2011) demonstrated that for the imaging of larger species clinical MRI at 1.5 T with 0.125 mm 3 spatial resolution is sufficient to display internal organs. Here, we present a non-invasive method to image and determine morphometric data on starfish in vivo using clinical MRI and subsequent 3D modeling.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, Ruffins et al (2007) produced a 3D atlas for quail development at an isotropic voxel resolution of 40-70 μm 3 using an 11.7 T pre-clinical MRI system. In contrast, Lauridsen et al (2011) demonstrated that for the imaging of larger species clinical MRI at 1.5 T with 0.125 mm 3 spatial resolution is sufficient to display internal organs. Here, we present a non-invasive method to image and determine morphometric data on starfish in vivo using clinical MRI and subsequent 3D modeling.…”
Section: Discussionmentioning
confidence: 96%
“…Such approaches have been successfully applied to the study of anuran (Rubinsky et al 1994a), chelonian (Rubinsky et al 1994b;Stecyk et al 2009), hexapod (Hart et al 2003), and aranean (Pohlmann et al 2007;Lauridsen et al 2011) species. For example, the following morphological features could be depicted in the case of chelonians: carapace, gall bladder, gut, lungs, liver, plastron, and ventricle (Stecyk et al 2009).…”
Section: In Vivo Mri Of Zoological Specimensmentioning
confidence: 99%
“…In the present study, we found that the more terrestrial species (Bufonidae) have relatively larger lungs (cf. Lauridsen et al, 2011) than either Ranidae or Pipidae, and are likely to be more effective at transmitting pressure to the surrounding lymph sacs during lung inflation. Inflation of the lungs in anesthetized animals causes increases in pressure of the lymph sacs surrounding the lungs , thus lung inflation would facilitate movement of lymph toward the lymph hearts by 'squeezing' lymph sacs against the body wall.…”
Section: The Role Of Pulmonary Compliance and Lung Volume In Lymph Momentioning
confidence: 99%
“…Breviceps spp.) (see Hillman et al, 2009), and their lungs occupy a large fraction of the pleuroperitoneal space (Lauridsen et al, 2011). Thus, lung volume relative to body mass should be largest for globose anurans, but nevertheless large for other amphibians, although this has not been systematically examined.…”
Section: Introductionmentioning
confidence: 99%